ASSESSMENT OF THE TECHNOLOGICAL CAPABILITIES OF MODERN CHEMICAL MATERIALS FOR LIQUID FINISHING OF LEATHER - ZAIETS, ANTONINA; ANDREYEVA, OLGA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Natural leather is a by-product of the meat industry, which turns into a valuable product that has high strength, stability, comfort, breathability and is considered one of the best products of the circular economy. In addition, less materials from non-renewable sources are used in leather production than in other industries, recycling of waste is practiced, which contributes to the protection of the environment and sustainable development of society. The choice of processing method, type of equipment and chemical materials is of great importance for the quality of leather and the ecological imperative of its manufacturing technology. At the same time, despite the progress of modern chemical technology, the leather industry constantly needs to find and introduce new, more effective means, which would not only be stable in their properties, available and compatible with the components of the «collagen-chemical material» system, but would also contribute the formation of this system in the direction of creating quality products while reducing the harmful load on the environment. The results of previous studies indicate the prospects of modified liquor materials and polymer compounds. Taking into account the above, the technological capabilities of modern commercial chemical materials - modified fats of various origins and acrylic polymer - were analyzed by using them in the liquid decoration of semi-finished Wet-blue half skin. Using the methods of organoleptic assessment, chemical analysis, physico-mechanical tests and microscopy, the advantages of these materials compared to those known during retanning-filling and liquoring have been established. The improvement of the indicators of the content of unbound fat in the leather, the limit of tensile strength and elongation at a stress of 10 MPa was revealed. Good elastic-plastic properties and no difference between the strength of the test skins as a whole and their front layer indicate a more even distribution of materials in the structure of the dermis. This correlates with the results of microscopic studies and allows predicting an increase in area yield, that is, a more rational use of scarce leather raw materials. The results of the work will be used in further studies devoted to the optimization of the parameters of the technology of liquid finishing of natural leather.